The Presentation of Financial Statements Within the Framework of the Public Sector Accounting Standards: A Comparison of DMS, EPSAS, and IPSAS - Kuyumcu, Oğuz (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This study examines Türkiye's compliance with the European Public Sector Accounting Standards (EPSAS) in the context of its European Union (EU) membership process. While Türkiye has already aligned its public accounting system with International Public Sector Accounting Standards (IPSAS), the potential adoption of EPSAS introduces new regulatory challenges. The study analyzes the conceptual framework of public sector accounting standards, comparing EPSAS, IPSAS, and Türkiye’s existing regulations. A case study on a municipal financial reporting system is used to highlight practical differences. Findings indicate that while Türkiye’s IPSAS-based framework provides a strong foundation, full EPSAS alignment requires additional modifications to comply with EU-specific fiscal rules such as the Maastricht Criteria and the European System of Accounts. The study contributes to the discussion on international accounting harmonization and its implications for candidate countries.